2006
DOI: 10.1002/jnr.20847
|View full text |Cite
|
Sign up to set email alerts
|

Immunization does not interfere with uptake and transport by motor neurons of the binding fragment of tetanus toxin

Abstract: The nontoxic binding domain of tetanus toxin (fragment C or TTC) readily undergoes retrograde axonal transport from an intramuscular injection site. This property has led to investigation of TTC as a possible vector for delivering therapeutic proteins to motor neurons. However, the vast majority of individuals in the developed world have been vaccinated with tetanus toxoid and have circulating antitetanus antibodies that cross-react with TTC and may block the delivery of a TTC-linked therapeutic protein. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This allowed a small part of TTFC to be internalized and to reach the MN. Results have shown that vaccinated and unvaccinated animals presented detectable retrograde transport of TTFC using fluorimetry [72]. This demonstrated that at a high dose, TTFC could be used as a carrier for delivery of bioactive molecules into CNS even in vaccinated individuals.…”
Section: Immunological Properties Against Tetanusmentioning
confidence: 89%
See 1 more Smart Citation
“…This allowed a small part of TTFC to be internalized and to reach the MN. Results have shown that vaccinated and unvaccinated animals presented detectable retrograde transport of TTFC using fluorimetry [72]. This demonstrated that at a high dose, TTFC could be used as a carrier for delivery of bioactive molecules into CNS even in vaccinated individuals.…”
Section: Immunological Properties Against Tetanusmentioning
confidence: 89%
“…Because TTFC contains many epitopes, its use as a carrier to deliver molecules to the CNS may be delicate in vaccinated individuals. Studies have been conducted to analyze the immunogenic side effects of the administration of TTFC in vaccinated animals [72]. They revealed that the amount of injected TTFC as a carrier (molar equivalent) generally exceeds 10,000 times the lethal dose of TT in a mouse model, and neutralization of all the TTFC injected was unlikely even for a vaccinated animal.…”
Section: Immunological Properties Against Tetanusmentioning
confidence: 99%
“…However, a potential hurdle to consider in moving this to the clinic is the presence of neutralizing antibodies in the sera of most individuals in North America and Europe, a consequence of widespread tetanus vaccination. To ascertain whether tetanus vaccination affects retrograde uptake of TTC, Fishman et al quantified transported rhodamine‐labeled TTC in the hypoglossal with TT 52 . Despite elevated titers of antibody against TTC in the vaccinated animals, the net uptake of TTC in the hypoglossal nucleus was readily detected and not reduced by vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Most individuals in the developed world are vaccinated against tetanus, and even for those that are not, treatments in humans are expected to be long term when natural immunogenicity of TTC may become a problem. However, uptake of TTC by nerve terminals from an intramuscular depot is rapid and is not blocked by immunization against tetanus toxoid in mice [113]. Rapid neural internalization may protect TTC and conjugated passenger molecules by making them inaccessible to the antibodies.…”
Section: Future Directionsmentioning
confidence: 99%